Science Education and the Scientific Revolution: a way to learn about Science - MICHAEL R. MATTHEWS (Metaichmio Publications, 2007)
This paper documents some of the international curriculum documents that require that science students learn about science - its methodology, relations with wider culture, technology and worldviews - as well as learning the content and process skills of science. This wider, or cultural, goal for science courses amounts to students learning something about the history and philosophy of their subject. It is argued that some study of the Scientific Revolution is a very appropriate and rich way to forward this cultural goal. The example of the seventeenth-century debate about the shape of the earth is used to illustrate significant features of the scientific revolution, and consequently enduring features of modern science.